The role of wage bargaining institutions in the Phillips curve Flattening - De Palma, Francesco (2022)
We investigate the role of collective wage bargaining institutions on the relationship between wage growth and unemployment, that is, the wage Phillips curve. Based on a labour market model with frictions and collective bargaining, we hypothesize that when the economy deteriorates, wages fall less in parts of the economy covered by collective wage agreements negotiated by trade unions at a centralized level than in economies with bargaining fully decentralized within companies. We move from theory to empirical analysis using regional NUTS-2 data from European countries, which show evidence that the wage Phillips curve flattens when unemployment is high — and gets steeper when the labor market is overheated —, in economies where the sectoral or cross-sectoral levels play a role in the collective wage bargaining. We also find that from a level of centralization intermediate between the company and the sector levels, the wage Phillips curve is twice as flat.